CANPA: Computer-Assisted Natural Products Anticipation - Ramos, AEF (2019)
This work has been developed with the funding from Cienciactiva, an initiative of the National Council for Science, Technology and Technological Innovation (CONCYTEC) contract 239-2015-FONDECYT. This was also supported by the French ANR grant (ANR-15-CE29-0001). We express our thanks to Jean-Christophe Jullian (BioCIS) for performing the NMR analysis of the isolated compounds. We also thank Karine Leblanc (BioCIS) for her assistance in the preparative HPLC purifications. We are very grateful to North Province of New Caledonia and Falconbridge New Caledonia that have facilitated our field investigation.